1997
DOI: 10.1115/1.2824120
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prandtl Numbers on Local and Average Convective Heat Transfer Characteristics in Helical Pipes

Abstract: To investigate the effects of the Prandtl number and geometric parameters on the local and average convective heat transfer characteristics in helical pipes, experiments with three different fluids—air, water, and ethylene glycol—were carried out on five uniformly heated helical pipes. The test sections were made from 22.9 mm I.D. and 10.2 mm I.D. 304 stainless steel pipes. The ratios of the pipe diameter and pitch to coil diameter (d/D and b/D) ranged from 0.0267 to 0.0884 and 0.20 to 2.56, respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
72
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(81 citation statements)
references
References 18 publications
9
72
0
Order By: Relevance
“…The results indicated that the presence of torsion has large effects on flow field and heat transfer if the ratio of curvature to torsion is of order unity. Xin and Ebadian [3] tested five helical pipes with different torsions and curvature ratios to investigate local and averaged heat transfer characteristics. They found that the temperature distribution becomes fully developed after two turns from the inlet.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the presence of torsion has large effects on flow field and heat transfer if the ratio of curvature to torsion is of order unity. Xin and Ebadian [3] tested five helical pipes with different torsions and curvature ratios to investigate local and averaged heat transfer characteristics. They found that the temperature distribution becomes fully developed after two turns from the inlet.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the Reynolds number and pitch of the coiled tube on the heat transfer coefficient were investigated. Xin et al (5) studied the effects of the Prandtl numbers and geometric parameters on the local and average convective heat transfer characteristics in helical-pipes. The experiments were performed with three different working fluids: air, water, and ethylene-glycol.…”
Section: Introductionmentioning
confidence: 99%
“…Roger and Mayhev's correlation [14] has greater error than Xin and Ebadian's correlation [15]. These correlations, as already said, are the only ones that directly take into account the curvature of the heat exchanger.…”
Section: Comparison With Empirical Correlationsmentioning
confidence: 84%
“…Xin and Ebadian [15] presented an experimental study on heat transfer for helical tubes. The correlation proposed by them, which is valid for both air and water, with 0.7 \ Pr \ 5 and Reynolds between 5.5 9 10 3 and 1.1 9 10 5 and cooled fluid, is:…”
Section: Empiric Correlation Researchedmentioning
confidence: 99%